Genetic engineering – yes or no for modification of our food - Macewicz, Jerzy (Studia Ecologiae et Bioethicae, 2003)
The discussion about genetic engineering became present in mass media in UE and the USA. Scientists didn't meet with public opinion approval when they started changing radically the food that we consume. But neither public opinion nor UE or Polish legislation keeps pace with the great development of food biotechnology. Students should take part in a dialog with arguments of supporters and opponents of GM food. The main goal of this education is to show achievements, changes, perspectives, and risks connected with GM food. As a result of this education, students should have knowledge about issues presented in the article, which also includes the content of lectures in the Faculty of the Environmental Protection in UKSW. GM food is causing extreme reaction: from absolute optimism to fierce opposition. While enthusiasts are showing large, unprecedented possibilities, skeptics remind us about the danger for us and future generations. The risk connected with GM food is still unknown. And the effects of manipulations will be irrevocable and lasting. Then there is a chance to hear arguments of biotechnologists and their fierce adversaries - ecologists.